Computer Engineering 3KB3: Optimization, Vol. 1 - Bandler, John W. (Simulation Optimization Systems Research Laboratory, 1993)
This courseware is designed to familiarize students with a wide range of concepts and techniques applicable to engineering design optimization in general, and electrical circuit and system design problems in particular. It is the cumulative product to 1993 of Bandler’s teaching, research, and innovation at McMaster University. Chapters within this text include: Chapter 1: Introduction (problem formulation); Chapter 2: Vectors, matrices and sensitivities; Chapter 3: Solving equations (linear, nonlinear, and differential); Chapter 4: Fundamentals of optimization (objective functions, constraints, minimax approximation, conditions for optimality); Chapter 5: Algorithms (one-dimensional, multi-dimensional, gradient, non-gradient); Chapter 6: Simulation (linear and nonlinear systems, including sensitivity analysis, first-order and large change); Chapter 7: Sensitivity analysis of linear networks, including the state of the art of adjoint network techniques.
Custom Courseware prepared by John Bandler for Computer Engineering 3KB3: Computational Methods II, for the winter 1994 Session. Some materials were previously available in early 1993 as individual texts used in Computer Engineering courses 3KB3: Computational Methods II and 4KC3: Simulation and Optimization.
Keywords: computer engineering; courseware; computer-aided design; optimization; simulation; sensitivity analysis; circuit optimization; minimax; least pth; design automation; iterative methods; adjoint networks